The Perceptions of Students and Principals on the Improvement of Students’ Achievements by the Managerial and Transformational Leadership Styles - Xhomara, Nazmi; Karabina, Mirela; Hasani, Nazyktere (Pedagogika, 2023)
The study aimed to investigate the impact of managerial and transformational leadership styles on students’ achievements. The quantitative approach, a structured questionnaire, and a random cluster sample of respondents were used in the study. The study indicated a positive correlation between managerial leadership and students‘ achievements. At the same time, the study revealed that 9.9% of the variance according to students and 44.4% according to principals on students‘ achievements is explained by managerial leadership.